Near Net Shaping of Monolithic and Composite MAX Phases by Injection Molding. Issue 10 (30th August 2016) - Gonzalez‐Julian, Jesus; Classen, Lukas; Bram, Martin; Vaßen, Robert; Guillon, Olivier
Abstract : Injection molding of Ti3 SiC2, Ti2 AlC, and Ti2 AlC containing 10 wt% of SiC fibers has been investigated to enable the production of reliable complex near net shaped components. Gear wheels with 9 cogs, 32 mm external diameter, and 4 mm thickness have been successfully produced by injection and sintering, obtaining homogeneous components with the characteristic layered structure of the MAX phases and good surface quality with average roughness below 2 μm. Injection molding of MAX phases is reported for the first time, offering the potential for large‐scale production of functional parts for these compounds at affordable prices.